The Effect of Add-on Garcinia mangostana L. Extract on Endothelial Dysfunction in Type 2 Diabetes Mellitus Subjects with High Risk Framingham Score: A Cohort Study - Olivia Handayani; Djanggan Sargowo; Mohammad Saifur Rohman; Budi Satrijo; Cholid Tri Tjahjono; Dadang Hendrawan (Universitas Brawijaya, 2020)
Background : Garcinia mangostana L. has been extensively used for years as antioxidant and anti-inflammation. However, its role in the context of endothelial disease was lacking.Objectives : To assess the effect of add-on G. mangostana L. extracts on endothelial dysfunction in type 2 diabetes subjects with high-risk Framingham score, compared to placebo.Methods : This was a prospective cohort study conducted in type 2 diabetes subjects with high-risk Framingham score. Subjects were randomized into two groups. The first group received 2,520 mg/day of G. mangostana L. extract. The second group was given a placebo for 90 days. The outcome measure of our study was the levels of endothelial progenitor cell (EPC), circulating endothelial cell (CEC), nitric oxide (NO), tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), IL-6, hemoglobin A1c (HbA1c), high-sensitivity C-reactive protein (hs-CRP), malondialdehyde (MDA), Superoxide dismutase (SOD) and fasting blood glucose. Multiple linear regression was used to determine the correlation and effect estimate.Results: A total of 49 patients were included in our study. Of those, elevated levels of EPC and SOD were observed in treatment group compared to placebo. On the other hand, the level of CEC, IL-1, Il-6, NO, MDA, TNF-α, fasting blood glucose and HbA1c was found significantly lower than placebo.Conclusion: Garcinia mangostana L. extract is associated with an increased levels of EPC and SOD, and it is also correlated with a decreased levels of CEC, IL-1, Il-6, NO, MDA, TNF-α, fasting blood glucose and HbA1c.